Investigating English Teacher Candidate’s Use of Instructional Media During the Teaching Practicum: A Case Study - Rachel Ratih Ayu T; Zakiyah Tasnim; Annur Rofiq (Pancaran Pendidikan, 2020)
This study analyzes the English teacher candidate’s use of instructional media in the teaching practicum. The English teacher candidate who became the participant in this study was doing their teaching practicum in MTsN 5 Jember. This study applied the qualitative case study design. Interview and observation were done one time to select the participant. The four-times classroom observations and questionnaires were used in order to collect the data. This study employed the model of Creswell in analyzing the data. The findings of this study showed that the English teacher candidate applied one type of instructional media namely Visual Media. Those were Picture and Whiteboard. The way the teacher candidate implemented the instructional media was almost the same in each meeting of the teaching and learning process. However, the students’ participation and response were not always the same in every meeting. It depended on the way the teacher candidate managed the class activity.